2017
DOI: 10.1007/s00784-017-2056-8
|View full text |Cite
|
Sign up to set email alerts
|

Gingival recessions of lower incisors after proclination by orthodontics alone or in combination with anterior mandibular alveolar process distraction osteogenesis

Abstract: During orthodontic treatment, with or without DO, one should avoid proclining lower incisors more than 10° to decrease the risk of gingival recessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Looking specifically at lower incisors, very little has been published so far. Nevertheless, the present magnitude (mean 0.0-0.1 mm, maximum 1.0 mm) is similar or lower than in class II:1 patients after Herbst-MBA Tx (mean 0.1-0.2 mm, maximum 4.0 mm [18]) respectively in other samples of orthodontically treated patients observed for 4-9 years where the values in the literature range between ≈ 0.6 mm [41], 0.6-1.1 mm [12] and 0.9-1.0 mm [42]. This is also true for the corresponding values determined from an orthodontically untreated sample (mean 1.0-1.2 mm, maximum 3.0 mm [29]).…”
Section: Results-magnitudesupporting
confidence: 45%
“…Looking specifically at lower incisors, very little has been published so far. Nevertheless, the present magnitude (mean 0.0-0.1 mm, maximum 1.0 mm) is similar or lower than in class II:1 patients after Herbst-MBA Tx (mean 0.1-0.2 mm, maximum 4.0 mm [18]) respectively in other samples of orthodontically treated patients observed for 4-9 years where the values in the literature range between ≈ 0.6 mm [41], 0.6-1.1 mm [12] and 0.9-1.0 mm [42]. This is also true for the corresponding values determined from an orthodontically untreated sample (mean 1.0-1.2 mm, maximum 3.0 mm [29]).…”
Section: Results-magnitudesupporting
confidence: 45%
“…The initial tooth displacement due to orthodontic force determines, especially in the early stages of OTM [2,4], the increase of stress in the periodontal ligament which determines the osteogenic response of the alveolar bone responsible for the subsequent tissue remodeling [7,8,9]. This could result in a significant reduction in the speed of OTM and in related phenomena such as in gingivitis, dental ankyloses, and root resorption [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between incisor inclination and their crown length was statistically significant (p = 0.027), which agrees with the results from the present study. Antonarakis et al [3] followed 55 patients over an average of 4.5 years after orthodontic treatment, reporting an increase in the labial gingival recessions. Multiple regression analysis showed that younger individuals, girls, and patients with greater incisor proclination were at higher risk of recession.…”
Section: Discussionmentioning
confidence: 99%